AN INVESTIGATION INTO LINGUISTIC FEATURES OF SPEECH ACT VERBS IN ENGLISH AND VIETNAMESE NEWSPAPER NEWS (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis has been carried out with the hope to bring about more detailed linguistic analysis of a variety of speech act verbs in the representative and expressive classes in newspaper news where human communication is much reflected. We conduct the research based on the statistics and analysis of using speech act verbs in pieces of news in English in English newpapers and pieces of news in Vietnamese in Vietnamese newspapers. We collected 100 pieces of news in English newspaper and 100 pieces of news in Vietnamese newspaper. Each piece of news has about from 400 words to 500 words. These pieces of news were collected from official newspapers in the United States and in Viet Nam such as The New York Times, The Washington Post, Lao Dong, Nhan Dan. Through this research, we find out a mass of typical speech act verbs in both languages: English and Vietnamese, how they are employed and the reasons for journalists’ choice of speech act verbs newspaper news. These things were presented with statistics expressing the distribution of speech act verbs, the frequency of occurrence of speech act verbs of the two types: performative verbs and reporting verbs in each class of speech act verbs. The result of the investigation was also shown with statistical tables of the occurrence of sentence patterns containing speech act verbs in each language and so on. Besides, the research presented an analysis of semantic and pragmatic features of speech act verbs in each language as well as principles or tips of writing broadcast news. The research also displayed similarities and differences between English and Vietnamese speech act verbs innewspaper news to help readers to approach features of this kind of verbs in each or between the two language communities. Furthermore, the result of the investigation also contributes to orienting the use of speech act verbs in language teaching, learning and writing broadcast news. Teachers and learners have oppotunities to explore and master linguistic features of each speech act verb to support their work and study or daily communication. Students of journalism can use correct verbs in newspaper news for their future work